Amygdala volume mediates the relationship between externalizing symptoms and daily smoking in adolescence: A prospective study. (30th June 2018) - Cheetham, Ali; Allen, Nicholas B.; Whittle, Sarah; Simmons, Julian; Yücel, Murat; Lubman, Dan I.
Highlights: Daily smoking at age 18 was predicted by externalizing behaviors at age 12. This relationship was mediated by smaller volumes of the right amygdala. These factors may be associated with vulnerability to substance use disorders. Abstract: The current study examined amygdala and orbitofrontal cortex (OFC) volumes as mediators of the relationship between externalizing symptoms and daily smoking in adolescence. Externalizing behaviors are among the most robust predictors of adolescent smoking, and there is emerging evidence that volume reductions in the amygdala and OFC are associated with risk for substance misuse as well as aggressive, impulsive, and disinhibited tendencies. Using a prospective longitudinal design, we recruited 109 adolescents who provided data on brain volume and externalizing behaviors at age 12, and on smoking at age 18. Daily smoking at age 18 ( n  = 27) was predicted by externalizing behaviors (measured by the self-report Child Behavior Checklist, CBCL) as well as smaller right amygdala volumes. Right amygdala volumes mediated the relationship between externalizing symptoms and later smoking. These findings provide important insight into the neurobiological risk factors associated with adolescent smoking, and, more generally, into factors that may be associated with vulnerability to substance use disorders and related psychopathology.